Modelled connectivity between Walleye Pollock (Gadus chalcogrammus) spawning and age-0 nursery areas in warm and cold years with implications for juvenile survival. (16th March 2016) - Petrik, Colleen M.; Duffy-Anderson, Janet T.; Castruccio, Frederic; Curchitser, Enrique N.; Danielson, Seth L.; Hedstrom, Katherine; Mueter, Franz
Abstract: Adult and early life stage distributions of the commercially important demersal fish Walleye Pollock ( Gadus chalcogrammus ) have varied in relation to the warm and cold environmental conditions on the eastern Bering Sea (EBS) shelf. Previous modelling studies indicate that transport alone does not account for the disparate juvenile distributions in warm and cold years, but that spawning locations are important. Our objective was to determine the potential connectivity of EBS pollock spawning areas with juvenile nursery areas between warm and cold years from an 18-year hindcast (1995–2012). We calculated the connectivity between larval sources and juvenile positions that were produced by a coupled biological-physical individual-based model that simulated transport, growth, and vertical behavior of pollock from the egg until the juvenile stage. Three connectivity patterns were seen in most simulations: along-isobaths to the northwest, self-retention, and transport around the Pribilof Islands. The major differences in connectivity between warm and cold years, more northwards in warm years and more off-shelf in cold years, mimicked wind-driven flow characteristics of those years that were related to winter mean zonal position of the Aleutian Low. Connectivity relationships were more sensitive to spatial alterations in the spawning areas in cold years, while they were more responsive to spawn timing shifts in warm years. The strongest connectivity to advantageous juvenile habitats originated in the well-known spawning areas, but also in a less well-studied region on the Outer Shelf. This northern Outer Shelf region emerged as a very large sink of pollock reaching the juvenile transition from all spawning sources, suggesting more thorough sampling across multiple trophic levels of this potentially important juvenile pollock nursery is needed.